2016
DOI: 10.5253/arde.v104i2.a7
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Changes Underpinning the Population Decline of StarlingsSturnus vulgarisin The Netherlands

Abstract: Large scale declines in farmland bird populations are of major conservation concern in many European countries (Donald et al. 2001, Sanderson et al. 2013). Studies explaining the causes of these population changes often focus on changes in agricultural practices, such as increased levels of mechanization, changes in sowing and harvesting times and frequencies, pesticide use and drainage (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…On the fast-slow continuum of reproductive capacity, the common starling is the fastest of the seven species we selected: It starts reproducing at an age of one year. We used the mean survival and reproductive rates for the whole Dutch breeding population (Versluijs, van Turnhout, Kleijn, & van der Jeugd, 2016), distinguishing three separate periods: 1960-1978, 1978-1990, and 1990-2012. In the first period (1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978), the population grew at 10% per year. This was followed by a period where the population was relatively stable (1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990).…”
Section: Common Starlingmentioning
confidence: 99%
“…On the fast-slow continuum of reproductive capacity, the common starling is the fastest of the seven species we selected: It starts reproducing at an age of one year. We used the mean survival and reproductive rates for the whole Dutch breeding population (Versluijs, van Turnhout, Kleijn, & van der Jeugd, 2016), distinguishing three separate periods: 1960-1978, 1978-1990, and 1990-2012. In the first period (1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978), the population grew at 10% per year. This was followed by a period where the population was relatively stable (1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990).…”
Section: Common Starlingmentioning
confidence: 99%
“…In the Netherlands, over the period 1960-2012, there was an increase in the overall population from 1960 to 1978, a stable population from 1978 to 1990 but then a steady decline. Although there was no consistent trend in reproductive output and adult survival fluctuated irregularly, juvenile survival declined significantly, and this was attributed to changes in agricultural land use (Versluijs et al, 2016). Smith and Bruun (2002) had shown that the breeding success for Swedish starlings was greatest where they had easy access to pastures, which increased nestling survival, whereas other factors such as clutch size and the timing of breeding were not affected.…”
Section: Notesmentioning
confidence: 99%
“…The European starling (hereafter starling) is a highly invasive pest, introduced and successfully establishing on every other continent except Antarctica (Higgins et al, 2006 ). Despite this, native range starlings are themselves a conservation focus, with declines of more than 50% in some countries (Versluijs et al, 2016 ) putatively associated with shifts in farming practice that are common in their native range (Freeman et al, 2007 ; Heldbjerg et al, 2016 ). Fortunately, due to the historical popularity of collecting bird skins, historical starling samples may be found scattered across many museums and institutions in both their native range and within invaded countries.…”
Section: Introductionmentioning
confidence: 99%